Vegestation and flora diversities in Thung Rech, Kim Boi district, Hoa Binh province - Thuy, Tran Van; Duc, Nguyen Anh (Academia Journal of Biology, 2012)
Thung Rech vegetation covers on limestone and caster valley in high area at commune Tu Son, Kim Boi district, Hoa Binh province. To apply research traditional methods, such as principle structured forms - Ecology of UNESCO - 1973, Wittaker’s principle of component structure of the plant species (in 1962) and review ecosystems (Tansley, 1935) have been rated the resource of rich flora with 656 species belonging to 406 genus and 138 families of 5 phylum vascular of plant are Psilotophyta, Lycopodiophyta, Polypodiophyta, Pinophyta and Magnoliophyta. Although there is a variety of species, the density of individuals is so poor because its geological features are mainly limestone. Successions of vegetable plant including the recovery and the degradation are mainly secondary and complicated out of the impact of human being. Also, the ecosystem of the plant contains the vegetation communities’ specific to limestone northern Vietnam, it plays an important role in environmental protection, disaster reduction, balance, regulation of the flow and climate as well as the biodiversity conservation of the area. To need to build up the legal system and scientific measures to conserve the plant resources of this kind.